HYPERTHERMIA AND RADIATION THERAPY FOR LOCALLY ADVANCED OR RECURRENT BREAST CANCER - Refaat, Tamer (Breast, 2015)
INTRODUCTION: This study aims to report the outcome and toxicity of combined hyperthermia (HT) and radiation therapy (RT) in treatment of locally advanced or loco-regionally recurrent breast cancer. PATIENTS AND METHODS: Patients treated with HT and RT from January 1991 to December 2007 were reviewed. RT doses for previously irradiated patients were >40 Gy and for RT naïve patients >60 Gy, at 1.8–2 Gy/day. HT was planned for 2 sessions/week, immediately after RT, for a minimum of 20 minutes and for >4 sessions. Superficial or interstitial applicators were used with temperature measured by superficial or interstitial thermisters based on target thickness. HT treatment was assessed by thermal equivalent dose (TED), >42.5°C and >43°C. Endpoints included treatment response, lack of local progression (local control), and survival. RESULTS: 127 patients received HT and RT to 167 sites. These included the intact breast (24.4%), chest wall/skin (67.7%), and breast/chest wall and nodes (7.9%). At a median follow-up of 13 months (mean 30±38), improved overall survival was significantly associated with increasing RT dose (p<0.0001), median TED 42.5°C≥200 minutes (p=0.003), and local control (p=0.0002). Local control at last follow-up was seen in 55.1% of patients. Complete response was significantly associated with median TED 42.5°C≥200 minutes (p=0.002) and median TED 43°C≥100 minutes (p=0.03). CONCLUSION: HT and RT are effective for locally advanced or recurrent breast cancer in patients that have been historically difficult to treat by RT alone. Over 50% of patients achieved control of locoregional disease. Overall survival was improved with local control.